Binder polymer for non-aqueous secondary batteries, binder composition for non-aqueous secondary batteries, and non-aqueous secondary battery electrode
By using a binder polymer containing monomer (a1), monomer (a2) and polyrothane (a3) copolymer in a non-aqueous secondary battery, the problem of insufficient adhesion of the adhesive during the expansion and contraction of the electrode active material is solved, and the cycle characteristics and life of the battery are improved.
Patent Information
- Application Number
- CN202380049676.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-09
- Filing Date
- 2023-08-07
- Publication Date
- 2025-04-01
AI Technical Summary
The adhesive of the existing non-aqueous secondary battery is difficult to maintain good adhesion during the expansion and contraction of the electrode active material, resulting in poor circulation characteristics of the battery.
A non-aqueous secondary battery adhesive polymer containing monomer (a1), monomer (a2) and polyrothane (a3) is used, and the structural units of the polymer can slide and cross-link under stress to improve the adherence and adhesion of the adhesive.
By using this adhesive, the circulation characteristics of the electrode of the non-aqueous secondary battery can be significantly improved, the life of the battery can be extended, and the stability of the discharge capacity of the battery can be improved.
Smart Images

Figure CN119744456A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a binder polymer for a non-aqueous secondary battery, a binder composition for a non-aqueous secondary battery, a non-aqueous secondary battery electrode, a non-aqueous secondary battery, and a method for producing a binder polymer for a non-aqueous secondary battery.
[0002] This application claims priority based on Japanese Patent Application No. 2022-126956 filed in Japan on August 9, 2022, the contents of which are incorporated herein by reference. Background Art
[0003] Non-aqueous secondary batteries are widely used as power sources for notebook personal computers, mobile phones, power tools, electronic / communication equipment, etc., because they can be miniaturized and lightweight. In recent years, non-aqueous secondary batteries have also been used as power sources for electric vehicles and hybrid vehicles. As a representative example of non-aqueous secondary batteries, lithium-ion secondary batteries can be cited.
[0004] A non-aqueous secondary battery comprises a positive electrode with a metal oxide or the like as an active material, a negative electrode with a carbon material such as graphite as an active material, and an electrolyte. The positive electrode and the negative electrode are provided with a current collector and an electrode active material layer formed on the current collector. The electrode active material layer generally comprises a binder for bonding the active materials to each other and to the current collector, thereby fixing the electrode active material layer on the current collector.
[0005] Conventionally, as binders used in non-aqueous secondary batteries, those described in Patent Documents 1 and 2 are known.
[0006] Patent Document 1 describes a secondary battery electrode binder composition comprising 100 parts by mass of at least one polymer aqueous dispersion selected from styrene butadiene copolymer latex and acrylic emulsion, and 1 to 20 parts by mass of a compound having a cloud point of 70° C. or less.
[0007] Patent document 2 describes an adhesive for lithium ion secondary battery electrodes having a glass transition temperature of less than 30°C, wherein the adhesive for lithium ion secondary battery electrodes is obtained by emulsion polymerization of ethylenically unsaturated monomers containing 15 to 70% by mass of styrene, ethylenically unsaturated carboxylic acid esters, ethylenically unsaturated carboxylic acids and internal crosslinking agents as essential components in the presence of a surfactant.
[0008] In addition, Patent Document 3 describes a coating resin emulsion that can be suitably used for building exterior coatings, etc. Patent Document 3 discloses a coating resin emulsion, wherein the glass transition temperature of the resin constituting the coating resin emulsion is 0°C or higher, and the coating resin emulsion contains 0.01 to 4% by mass of a structural unit derived from a modified polyrotaxane, wherein the modified polyrotaxane has a structure in which a functional group having a radical polymerizable group is bonded to a cyclic molecule of a polyrotaxane having a cyclic molecule and a chain molecule penetrating an opening of the cyclic molecule and having a capping group at both ends.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2014-239070
[0012] Patent Document 2: Japanese Patent Application Publication No. 2011-243464
[0013] Patent Document 3: Japanese Patent Application Publication No. 2019-116594 Summary of the invention
[0014] Problems to be solved by the invention
[0015] In recent years, nonaqueous secondary batteries have been strongly required to have higher output, higher capacity, longer life, etc. Binders used in nonaqueous secondary batteries are required to improve the cycle characteristics of nonaqueous secondary batteries having electrodes using the binders.
[0016] The present invention is proposed in view of the above situation, and its purpose is to provide a binder polymer for a non-aqueous secondary battery that can be used as a binder material for forming an electrode of a non-aqueous secondary battery that can obtain excellent cycle characteristics, a binder composition for a non-aqueous secondary battery containing the binder polymer for a non-aqueous secondary battery, a slurry for a non-aqueous secondary battery electrode, and a method for producing a binder polymer for a non-aqueous secondary battery.
[0017] Another object of the present invention is to provide a nonaqueous secondary battery electrode comprising the nonaqueous secondary battery binder polymer of the present invention and capable of obtaining a nonaqueous secondary battery with excellent cycle characteristics, and a nonaqueous secondary battery having the nonaqueous secondary battery electrode.
[0018] Means for solving problems
[0019] The present invention includes the following aspects.
[0020] A first aspect of the present invention provides the following binder polymer for a non-aqueous secondary battery.
[0021] [1] A binder polymer for a non-aqueous secondary battery, characterized in that it has:
[0022] The first structural unit derived from monomer (a1);
[0023] a second structural unit derived from monomer (a2); and
[0024] The third structural unit derived from monomer (a3),
[0025] The monomer (a1) is a nonionic compound having only one ethylenically unsaturated bond.
[0026] The monomer (a2) is a compound having a carboxyl group and having only one ethylenically unsaturated bond.
[0027] The monomer (a3) is a polyrotaxane having a cyclic molecule and a chain molecule, wherein the cyclic molecule has a cyclic skeleton to which a group containing an ethylenically unsaturated bond is bonded, and the chain molecule penetrates the opening of the cyclic molecule and has end-capping groups at both ends.
[0028] The nonaqueous secondary battery binder polymer of the first aspect of the present invention preferably has the features described in [2] to
[16] below. It is also preferred that any two or more of the features described in [2] to
[16] below are combined.
[0029] [2] The binder polymer for a nonaqueous secondary battery according to [1], wherein at least one of the groups containing an ethylenically unsaturated bond bonded to the cyclic skeleton is a (meth)acryloyl group, a vinyl group, an allyl group, or an acryl group.
[0030] [3] The binder polymer for a nonaqueous secondary battery according to [1], wherein at least one of the groups containing an ethylenically unsaturated bond bonded to the cyclic skeleton is a (meth)acryloyl group.
[0031] [4] The binder polymer for a nonaqueous secondary battery according to any one of [1] to [3], wherein at least one of the cyclic skeletons in the cyclic molecule of the monomer (a3) is a crown ether skeleton, a cyclic siloxane skeleton, or a cyclic oligosaccharide skeleton.
[0032] [5] The binder polymer for a nonaqueous secondary battery according to any one of [1] to [3], wherein at least one of the cyclic skeletons in the cyclic molecule of the monomer (a3) is an α-cyclodextrin skeleton.
[0033] [6] The binder polymer for a nonaqueous secondary battery according to any one of [1] to [5], wherein at least one of the terminal blocking groups is a dinitrophenyl group, an adamantyl group, a trityl group, or a derivative group of any of these groups.
[0034] [7] The binder polymer for a non-aqueous secondary battery according to any one of [1] to [5], wherein at least one of the terminal blocking groups is an adamantyl group.
[0035] [8] The binder polymer for a non-aqueous secondary battery according to any one of [1] to [7], wherein the chain molecule is at least one selected from polyethylene glycol, polypropylene glycol, polyisoprene, polyisobutylene, polybutadiene, polytetrahydrofuran, polyacrylate, polydimethylsiloxane, polyethylene, and polypropylene.
[0036] [9] The binder polymer for a non-aqueous secondary battery according to any one of [1] to [7], wherein the chain molecule is polyethylene glycol.
[0037]
[10] The binder polymer for a non-aqueous secondary battery according to any one of [1] to [9], wherein the number average molecular weight of the chain molecule is 5,000 to 50,000.
[0038]
[11] The binder polymer for a non-aqueous secondary battery according to any one of [1] to
[10] , further comprising a fourth structural unit derived from a monomer (a4),
[0039] The monomer (a4) is a compound having a plurality of independent ethylenically unsaturated bonds.
[0040]
[12] The binder polymer for a non-aqueous secondary battery according to
[11] , wherein the content of the fourth structural unit in all structural units is 0.010 mass % or more and 10 mass % or less.
[0041]
[13] The binder polymer for a non-aqueous secondary battery according to any one of [1] to
[12] , wherein at least one of the monomers (a1) is an aromatic compound having an ethylenically unsaturated bond,
[0042] The content of the structural unit derived from the aromatic compound having an ethylenically unsaturated bond in all the structural units is 41% by mass or more.
[0043]
[14] The binder polymer for a nonaqueous secondary battery according to any one of [1] to
[13] , wherein the content of the second structural unit in all structural units is 0.10 mass % or more and 20 mass % or less.
[0044]
[15] The binder polymer for a nonaqueous secondary battery according to any one of [1] to
[14] , wherein the content of the third structural unit in all structural units is 0.010 mass % or more and 15 mass % or less.
[0045]
[16] The binder polymer for a non-aqueous secondary battery according to any one of [1] to
[15] , wherein the content of the third structural unit in all structural units is 4.1% by mass or more.
[0046] A second aspect of the present invention provides the following binder composition for a non-aqueous secondary battery.
[0047]
[17] A binder composition for a non-aqueous secondary battery, comprising: dispersed particles comprising the binder polymer for a non-aqueous secondary battery according to any one of [1] to
[16] ; and an aqueous medium.
[0048] The binder composition for a non-aqueous secondary battery according to the second aspect of the present invention preferably has the features described in the following
[18] .
[0049]
[18] The binder composition for a non-aqueous secondary battery according to
[17] , wherein the average particle size d50 of the dispersed particles is 0.18 μm or more and 1.0 μm or less.
[0050] A third aspect of the present invention provides the following slurry for nonaqueous secondary battery electrodes.
[0051]
[19] A slurry for a non-aqueous secondary battery electrode, comprising the binder polymer for a non-aqueous secondary battery according to any one of [1] to
[16] , an electrode active material, and an aqueous medium.
[0052] The aqueous medium is one selected from the group consisting of water, a hydrophilic solvent, and a mixture containing water and a hydrophilic solvent.
[0053] A fourth aspect of the present invention provides the following nonaqueous secondary battery electrode.
[0054]
[20] A non-aqueous secondary battery electrode comprising the binder polymer for a non-aqueous secondary battery according to any one of [1] to
[16] .
[0055] The nonaqueous secondary battery electrode according to the fourth aspect of the present invention preferably has the features described in the following
[21] .
[0056]
[21] A non-aqueous secondary battery comprising the non-aqueous secondary battery electrode described in
[20] .
[0057] A fifth aspect of the present invention provides the following method for producing a binder polymer for a non-aqueous secondary battery.
[0058]
[22] A method for producing a binder polymer for a non-aqueous secondary battery, characterized by comprising a polymerization step of copolymerizing a monomer comprising a monomer (a1), a monomer (a2), and a monomer (a3);
[0059] The monomer (a1) is a nonionic compound having only one ethylenically unsaturated bond.
[0060] The monomer (a2) is a compound having a carboxyl group and having only one ethylenically unsaturated bond.
[0061] The monomer (a3) is a polyrotaxane having a cyclic molecule and a chain molecule, wherein the cyclic molecule has a cyclic skeleton to which a group containing an ethylenically unsaturated bond is bonded, and the chain molecule penetrates the opening of the cyclic molecule and has end-capping groups at both ends.
[0062] Effects of the Invention
[0063] According to the present invention, a binder polymer for a nonaqueous secondary battery that can be used as a material for forming a binder for an electrode of a nonaqueous secondary battery that can provide excellent cycle characteristics and a method for producing the same can be provided.
[0064] Furthermore, according to the present invention, a binder composition for a non-aqueous secondary battery and a slurry for a non-aqueous secondary battery electrode that can provide a non-aqueous secondary battery with excellent cycle characteristics can be provided.
[0065] Furthermore, according to the present invention, it is possible to provide a nonaqueous secondary battery electrode capable of obtaining a nonaqueous secondary battery having excellent cycle characteristics, and a nonaqueous secondary battery having excellent cycle characteristics including the nonaqueous secondary battery electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 This is a schematic cross-sectional view for explaining the function of the binder composed of the binder polymer for non-aqueous secondary batteries of the present invention in the non-aqueous secondary battery electrode of the present invention.
[0067] Figure 2 This is a schematic diagram for explaining a polyrotaxane used as a raw material for the binder polymer for a non-aqueous secondary battery of the present invention. DETAILED DESCRIPTION
[0068] The present inventors have conducted intensive studies as described below in order to solve the above problems and realize a binder capable of forming a nonaqueous secondary battery electrode capable of obtaining a nonaqueous secondary battery with excellent cycle characteristics.
[0069] Figure 1 This is a schematic cross-sectional view for explaining the function of the binder composed of the binder polymer for non-aqueous secondary batteries of the present invention in the non-aqueous secondary battery electrode of the present invention.
[0070] Figure 1The non-aqueous secondary battery electrode (hereinafter sometimes referred to as "electrode") 20 shown includes a current collector 23 made of copper foil or the like, and an electrode active material layer 24 formed on the current collector 23. As one embodiment, the electrode active material layer 24 includes an electrode active material 22, a thickener 21, and a binder 25.
[0071] If the electrode active material layer 24 of the electrode 20 expands and contracts as the non-aqueous secondary battery is used, that is, due to the expansion and contraction of the electrode active material 22 during charge and discharge, and is separated from the current collector 23, the discharge capacity of the non-aqueous secondary battery having the electrode 20 decreases. In addition, even if the electrode active material layer 24 is not separated from the current collector 23, if the bonding between the electrode active materials 22 and between the electrode active material 22 and the current collector 23 becomes insufficient due to the expansion and contraction of the electrode active material 22, the discharge capacity of the non-aqueous secondary battery also decreases.
[0072] Therefore, the binder 25 is preferably a material that can maintain the binding properties between the electrode active materials 22 and between the electrode active material 22 and the current collector 23 for a long time and can form the electrode 20 in which the electrode active material layer 24 is not easily peeled off from the current collector 23 .
[0073] However, in the conventional technology, since the toughness of the binder 25 is insufficient, the binder 25 cannot follow the expansion and contraction of the electrode active material 22 accompanying charge and discharge.
[0074] The directions of expansion and contraction of the multiple electrode active materials 22 included in the electrode active material layer 24 are random. Therefore, most of the adhesive 25 included in the electrode active material layer 24 is configured between the electrode active materials 22 that expand and contract in different directions, and between the electrode active materials 22 that expand and contract in different directions and the collector 23. Therefore, if the adhesive 25 is not a material that has sufficient followability for each of the multiple materials that expand and contract in different directions that are connected via the adhesive 25, good adhesion cannot be obtained. In contrast, for example, in the case where a coating film containing an adhesive and not containing an electrode active material 22 is formed on a substrate, the adhesive in the coating film can be followed only along the direction of expansion and contraction of the substrate. Therefore, even if it is an adhesive that can be used as a material for a coating film that is not easy to be peeled off from a substrate, it may not have enough to fully obtain the followability of the adhesion between the electrode active materials 22 and the electrode active material 22 and the collector 23, and the electrode active material layer 24 containing the adhesive and the electrode active material 22 may not be easy to be peeled off from the collector 23.
[0075] Therefore, it is difficult to realize a binder 25 that has good bonding properties between the electrode active materials 22 and between the electrode active materials 22 and the current collector 23 and that prevents the electrode active material layer 24 from being easily peeled off from the current collector 23 in the prior art.
[0076] Therefore, the inventors of the present invention have conducted in-depth research on a binder comprising a polymer copolymerized by a monomer (a1) consisting of a nonionic compound having only one ethylenically unsaturated bond and a monomer (a2) consisting of a compound having an anionic functional group and only one ethylenically unsaturated bond, in order to easily obtain a polymer for an electrode active material layer 24 that is not easily peeled off from a collector 23 composed of copper foil or the like.
[0077] As a result, it was found that by using a monomer (a1), a monomer (a2), and Figure 2 A polymer obtained by copolymerizing the monomer (a3) constituting the polyrotaxane 10 described above may be used as a binder for a non-aqueous secondary battery.
[0078] Figure 2 This is a schematic diagram for explaining a polyrotaxane used as a raw material for the binder polymer for a non-aqueous secondary battery of the present invention.
[0079] Figure 2 The polyrotaxane 10 shown includes a cyclic molecule 1 having a cyclic skeleton to which a group 4 containing an ethylenically unsaturated bond is bonded, and a chain molecule 3 penetrating an opening 11 of the cyclic molecule 1 and having a capping group 2 at both ends. The following describes the function presumed by the inventors.
[0080] The above-mentioned monomer (a1), monomer (a2), and Figure 2 The polymer obtained by copolymerizing the monomer (a3) composed of the polyrotaxane 10 shown, the cyclic molecule 1 contained in the structural unit derived from the polyrotaxane 10 can move relative to the chain molecule 3. Therefore, for the above-mentioned polymer, if stress is applied to the polymer, the cross-linking points between the cyclic molecules 1 of the polyrotaxane 10 in the polymer and the cross-linking points between the cyclic molecules 1 and the monomer (a1) and / or the monomer (a2) in the polymer move relative to the chain molecule 3 (pulley effect), and the stress is dispersed. In addition, when the stress is applied to the polymer, the uncross-linked cyclic molecules 1 in the polymer move, and if the distance between the uncross-linked cyclic molecules 1 on the chain molecule 3 is close, an air spring effect is exhibited to maintain the distance between the uncross-linked cyclic molecules 1 on the chain molecule 3, and the recovery is performed.
[0081] Therefore, the binder composed of the above polymer has the ability to follow the expansion and contraction of the electrode active material 22 accompanying the use of the non-aqueous secondary battery due to the structural unit derived from the polyrotaxane 10. As a result, it is estimated that the electrode active material layer 24 including the binder composed of the above polymer obtains the following functions <1> <2>.
[0082] <1> Due to the followability of the structural unit derived from the polyrotaxane 10, the retention force of the electrode active material 22 generated by the binder 25 between the electrode active materials 22 in the electrode active material layer 24 and between the electrode active material 22 and the collector 23 is improved, and even if the electrode active material 22 expands or contracts, the adhesion between the electrode active materials 22 and between the electrode active material 22 and the collector 23 is maintained for a long time.
[0083] <2> Even if the electrode active material layer 24 expands and contracts due to the expansion and contraction of the electrode active material 22, the conformability of the structural unit derived from the polyrotaxane 10 effectively exerts the adhesion to the collector 23 due to the structural units derived from the monomers (a1) and (a2), and the electrode active material layer 24 is not easily peeled off from the collector 23.
[0084] Furthermore, the inventors of the present invention manufactured an electrode using the above-mentioned polymer as a binder for a non-aqueous secondary battery, and confirmed that: an electrode with good adhesion between electrode active materials and between electrode active materials and current collectors can be formed, and the electrode active material layer is not easily peeled off from the current collector; the non-aqueous secondary battery having the electrode has excellent cycle characteristics, which led to the present invention.
[0085] The following is a detailed description of the non-aqueous secondary battery binder polymer and its manufacturing method, the non-aqueous secondary battery binder composition, the non-aqueous secondary battery electrode slurry, the non-aqueous secondary battery electrode and the non-aqueous secondary battery of the present invention. In addition, the present invention is not limited to the embodiments shown below. For example, the present invention can add, omit, replace, and change the number, amount, position, ratio, material, composition, type, order, etc. within the scope of the purpose of the present invention.
[0086] Here, the following terms used in this specification are explained.
[0087] The term "(meth)acrylic acid" is a general term for acrylic acid and methacrylic acid, and the term "(meth)acrylate" is a general term for acrylate and methacrylate.
[0088] The "ethylenically unsaturated bond" means an ethylenically unsaturated bond having free radical polymerizability unless otherwise specified.
[0089] In a polymer using a compound having an ethylenically unsaturated bond, the structural unit derived from the compound having an ethylenically unsaturated bond may refer to a chemical structure of a portion other than the ethylenically unsaturated bond in the compound, or a structural unit having the same chemical structure as the portion of the structural unit in the polymer other than the portion corresponding to the ethylenically unsaturated bond. The ethylenically unsaturated bond of the compound may be changed to a single bond when forming a polymer. For example, in a polymer of methyl methacrylate, the structural unit derived from methyl methacrylate is represented by -CH2-C(CH3)(COOCH3)-.
[0090] In addition, in the case of a polymer of a compound having an ionic functional group and an ethylenically unsaturated bond, for example, a structural unit having an ionic functional group such as a carboxyl group as the second structural unit described later may be a structural unit derived from the same ionic compound, whether or not a part of the functional group is ion-exchanged. For example, a structural unit represented by -CH2-C(CH3)(COONa)- can also be considered to be a structural unit derived from methacrylic acid.
[0091] In addition, regarding the compound with independent multiple ethylenically unsaturated bonds, as the structural unit of the polymer of the above-mentioned compound, more than one ethylenically unsaturated bond may remain in the structural unit. For example, in the case of a polymer of divinylbenzene, the structural unit derived from divinylbenzene may be a structure without ethylenically unsaturated bonds (the parts corresponding to the two ethylenically unsaturated bonds of divinylbenzene are both introduced into the chain of the polymer), or a structure with one ethylenically unsaturated bond (the part corresponding to only one ethylenically unsaturated bond is introduced into the chain of the polymer). Here, the so-called independent multiple ethylenically unsaturated bonds refer to multiple ethylenically unsaturated bonds that do not form conjugated dienes with each other.
[0092] Furthermore, after polymerization, when the functional groups other than the chain structure corresponding to the ethylenically unsaturated bond in the polymer, such as the carboxyl group, no longer correspond to the chemical structure of the monomer due to a chemical reaction, the structural unit of the polymer is set to a structural unit derived from a compound having an ethylenically unsaturated bond in the polymer. For example, when vinyl acetate is polymerized and then saponified, the structural unit of the polymer is set to a structural unit derived from vinyl alcohol rather than a structural unit derived from vinyl acetate, taking the chemical structure of the polymer as a reference.
[0093] In the present embodiment, the term "class" added to the name of a compound refers to a group of compounds including the structure of the compound, and also includes the compound having a substituent.
[0094] <1. Binder polymer for non-aqueous secondary batteries (P)>
[0095] The non-aqueous secondary battery binder polymer of the present embodiment is a polymer used as a binder for a non-aqueous secondary battery, and is sometimes referred to as "binder polymer (P)" hereinafter. The binder polymer (P) of the present embodiment has at least a first structural unit derived from a monomer (a1) shown below, a second structural unit derived from a monomer (a2) shown below, and a third structural unit derived from a monomer (a3) shown below.
[0096] The adhesive polymer (P) of the present embodiment may include, in addition to the first structural unit, the second structural unit, and the third structural unit, a fourth structural unit derived from a monomer (a4) which is not equivalent to any of the monomers (a1) to (a3) and is composed of a compound having multiple independent ethylenically unsaturated bonds, and / or a fifth structural unit derived from another monomer (a5) which is not equivalent to any of the monomers (a1) to (a4).
[0097] [1st structural unit]
[0098] The first structural unit in the binder polymer (P) of the present embodiment is derived from the monomer (a1).
[0099] Monomer (a1) is a nonionic compound having only one ethylenically unsaturated bond. That is, monomer (a1) is a compound having neither anionic functional groups nor cationic functional groups. Monomer (a1) may be only one compound or a combination of two or more compounds.
[0100] As the monomer (a1), at least one of (meth)acrylate and an aromatic compound having an ethylenically unsaturated bond is preferably used, and a combination of the two compounds is more preferably used. The (meth)acrylate is more preferably an alkyl (meth)acrylate. The number of carbon atoms of the alkyl group in the alkyl (meth)acrylate is preferably 1 to 20. In this case, the monomer (a1) other than the alkyl (meth)acrylate and the aromatic compound having an ethylenically unsaturated bond described later may also be used in combination.
[0101] As the (meth)acrylic acid alkyl ester contained in the (meth)acrylic acid ester used as the monomer (a1), for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isobornyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, etc. Among them, in order to form a binder polymer (P) that can form an electrode active material layer with excellent electrolyte resistance, it is preferred to include 2-ethylhexyl acrylate.
[0102] As the aromatic compound having an ethylenically unsaturated bond used as the monomer (a1), for example, styrene, tert-butylstyrene, α-methylstyrene, p-methylstyrene, 1,1-diphenylethylene, etc. In the case where the monomer (a1) contains an aromatic vinyl compound, it is more preferable to contain at least one of styrene and α-methylstyrene, and in order to obtain a binder polymer (P) having excellent dispersibility in an aqueous medium, it is further preferable to contain styrene.
[0103] Examples of the monomer (a1) other than the (meth)acrylate and the aromatic compound having an ethylenically unsaturated bond include compounds having an ethylenically unsaturated bond and a polar functional group, aliphatic hydrocarbon compounds having an ethylenically unsaturated bond, and alicyclic hydrocarbon compounds having an ethylenically unsaturated bond.
[0104] The polar functional group in the compound having an ethylenically unsaturated bond and a polar functional group used as the monomer (a1) preferably contains at least one of a hydroxyl group and a cyano group, and more preferably contains a hydroxyl group.
[0105] The compound having an ethylenically unsaturated bond and a polar functional group used as the monomer (a1) includes, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, (meth)acrylonitrile, etc. In order to obtain good polymerization stability when producing the binder polymer (P), it is preferred to contain 2-hydroxyethyl methacrylate.
[0106] [Second structural unit]
[0107] The second structural unit in the binder polymer (P) of the present embodiment is derived from the monomer (a2).
[0108] The monomer (a2) is a compound having only one ethylenically unsaturated bond and a carboxyl group. The monomer (a2) may be only one kind of compound or a combination of two or more kinds of compounds.
[0109] As the monomer (a2), a compound having a plurality of carboxyl groups in one molecule may be used. That is, the binder polymer (P) may contain a plurality of carboxyl groups in one structural unit.
[0110] As the monomer (a2) having a carboxyl group, unsaturated monocarboxylic acids such as methacrylic acid, acrylic acid, and crotonic acid can be cited; unsaturated dicarboxylic acids such as itaconic acid and fumaric acid, etc. Among them, in order to form a binder polymer (P) that can form an electrode whose electrode active material layer is not easily peeled off from the collector, the monomer (a2) preferably uses at least one of acrylic acid, methacrylic acid, and itaconic acid.
[0111] At least a portion of the structural unit derived from the monomer (a2) can form a salt with an alkaline substance. As the monomer (a2) that forms a salt, for example, a metal salt, an ammonium salt of the monomer (a2) can be cited. As the metal of the metal salt, for example, an alkali metal such as lithium, sodium, potassium can be cited. As specific compounds, lithium (meth)acrylate, lithium itaconate, dilithium itaconate, sodium (meth)acrylate, sodium itaconate, disodium itaconate, ammonium (meth)acrylate, ammonium itaconate, diammonium itaconate, etc. can be cited.
[0112] [Third structural unit]
[0113] The third structural unit in the binder polymer (P) of this embodiment is derived from the monomer (a3). Figure 2 As shown, the monomer (a3) is a polyrotaxane including a cyclic molecule 1 and a chain molecule 3 penetrating an opening 11 of the cyclic molecule 1. The cyclic molecule 1 has a cyclic skeleton to which a group 4 including an ethylenically unsaturated bond is bonded. The chain molecule 3 has terminal groups 2 at both ends.
[0114] The monomer (a3) may be only one type of polyrotaxane, or may contain two or more types of polyrotaxanes.
[0115] The cyclic molecule 1 of the polyrotaxane 10 is Figure 2 As shown, it has an opening 11 through which the chain molecule 3 can pass. The cyclic molecule 1 can move along the chain molecule 3 while being penetrated by the chain molecule 3. The number of cyclic molecules 1 possessed by one molecule of polyrotaxane 10 is not particularly limited, and for example, it can be 1 to 500, 5 to 300, or 10 to 200. Further examples include 2 to 20, 3 to 40, 7 to 60, 15 to 100, and the like. When the number of cyclic molecules 1 is plural, the cyclic molecules 1 possessed by the polyrotaxane 10 may be only one type, or may be two or more types.
[0116] At least one of the cyclic skeletons possessed by the cyclic molecule 1 is preferably a crown ether skeleton, a cyclic siloxane skeleton, or a cyclic oligosaccharide skeleton. Among them, in order to obtain excellent reactivity when polymerizing the binder polymer (P), the cyclic skeleton is more preferably a cyclic oligosaccharide skeleton. Among the cyclic oligosaccharide skeletons, in order to obtain more excellent reactivity, an α-cyclodextrin skeleton is particularly preferred.
[0117] At least one of the groups 4 containing an ethylenically unsaturated bond bonded to the cyclic skeleton of the cyclic molecule 1 is preferably a (meth)acryloyl group, a vinyl group, an allyl group, or an acryl group. In order to obtain excellent reactivity when polymerizing the binder polymer (P), it is more preferably a (meth)acryloyl group. In order to obtain even better reactivity, it is further preferably an acryl group.
[0118] The group 4 containing an ethylenically unsaturated bond bonded to the cyclic skeleton may be bonded directly to the cyclic skeleton. Alternatively, the group 4 containing an ethylenically unsaturated bond bonded to the cyclic skeleton may be bonded to the cyclic skeleton via an arbitrary linking group.
[0119] The number of groups 4 containing ethylenically unsaturated bonds bound to the cyclic skeleton possessed by the cyclic molecule 1 may be one or more. When the number of groups 4 containing ethylenically unsaturated bonds bound to the cyclic skeleton is more than one, for example, it is preferably 50 or less, and more preferably 40 or less. For example, it may be 1 to 30, 2 to 20, 5 to 10, etc. In the present embodiment, since the number of groups 4 containing ethylenically unsaturated bonds bound to the cyclic skeleton possessed by the cyclic molecule 1 possessed by the polyrotaxane 10 is more than one, the cross-linking points between the cyclic molecules 1 of the polyrotaxane 10 and the cross-linking points between the cyclic molecules 1 and the monomer (a1) and / or the monomer (a2) can move relative to the chain molecule 3. As a result, a binder polymer (P) having the ability to follow the expansion and contraction of the electrode active material 22 is obtained. When the number of the groups 4 containing an ethylenically unsaturated bond bonded to the cyclic skeleton of the cyclic molecule 1 is 50 or less, the crosslinking density of the binder polymer (P) becomes appropriate, which is preferred.
[0120] The cyclic skeleton of the cyclic molecule 1 may have not only the group 4 containing an ethylenically unsaturated bond but also other substituents other than the group 4 containing an ethylenically unsaturated bond.
[0121] As other substituents, various organic groups can be mentioned. As organic groups, for example, hydrocarbon groups which may have a substituent having 1 or more carbon atoms can be mentioned. The number average molecular weight of the cyclic molecule 1 can be arbitrarily selected.
[0122] The chain molecule 3 included in the polyrotaxane 10 may be linear or branched.
[0123] The chain molecule 3 is preferably at least one selected from polyethylene glycol, polypropylene glycol, polyisoprene, polyisobutylene, polybutadiene, polytetrahydrofuran, polyacrylate, polydimethylsiloxane, polyethylene, and polypropylene. In order to better accommodate the function of the cyclic molecule 1 of the polyrotaxane 10, polyethylene glycol is more preferred.
[0124] The number average molecular weight of the chain molecule 3 is preferably 5,000 to 50,000, more preferably 7,500 to 40,000. It can be 10,000 to 30,000, 15,000 to 25,000, etc. If the number average molecular weight of the chain molecule 3 is 5,000 or more, the length of the chain molecule 3 can be sufficiently ensured. Therefore, in the binder polymer (P), the cross-linking points between the cyclic molecules 1 and the cross-linking points between the cyclic molecules 1 and the monomer (a1) and / or the monomer (a2) of the polyrotaxane 10 can be sufficiently lengthened relative to the distance that the chain molecule 3 moves. As a result, a binder polymer (P) having better followability to the expansion and contraction of the electrode active material is obtained. If the number average molecular weight of the chain molecule 3 is 50,000 or less, the cross-linking density of the binder polymer (P) is suitable, and therefore it is preferred.
[0125] The end-capping groups 2 of the polyrotaxane 10 have a function of preventing the cyclic molecules 1 from falling off from the chain molecules 3 due to their bulkiness and ionicity. The end-capping groups 2 disposed at both ends of the chain molecules 3 may be the same or different.
[0126] As the end-capping group 2 that prevents the cyclic molecule 1 from falling off from the chain molecule 3 by bulkiness, a group having a ring structure can be cited. At least one of the end-capping groups 2 is preferably a dinitrophenyl group, an adamantyl group, a trityl group, or a derivative group of any of them. In order to obtain excellent reactivity when polymerizing the binder polymer (P), it is more preferably an adamantyl group (which can be either 1-adamantyl group or 2-adamantyl group). The above-mentioned end-capping group 2 may further have a substituent. As the substituent that the end-capping group 2 may have, for example, an alkyl group, an alkyloxy group, a hydroxyl group, a halogen group, a cyano group, a sulfonyl group, a carboxyl group, an amino group, a phenyl group, etc. can be cited.
[0127] The polyrotaxane 10 can be produced using a known method.
[0128] Commercially available products may be used as the polyrotaxane 10. Examples of commercially available polyrotaxane 10 include "Celum (registered trademark) Super Polymer SM3403P", "Celum (registered trademark) Super Polymer SM1313P", and "Celum (registered trademark) Super Polymer SM1313P" commercially available from Adband Softerials Co., Ltd. "ルム(registered trademark)スーパーポリマーSA3403P", "セルム (registered trademark) "スーパーポリマーSA2403P" ”, “Surro(Registered Trademark)Surroman SA1313P”, “Surro(Registered Trademark)Surman SM3 405P", "セルム(registered trademark)キー・ミクスチャーSM3400C", "セルム(registered trademark)スーパーポリ"マーSA3405P", "セルム(registered trademark)スーパーポリマーSA2405P", "セルム(registered trademark)キー·ミクスチャーSA3400C", "セルム(registered trademark)キー·ミクスチャーSA2400C", "セルム(Note "Registered Trademark" "スーパーポリマーSA3405P"", "(Registered Trademark) "スーパーポリマーSA2405P"", etc.
[0129] Among these commercially available polyrotaxanes 10, in order to obtain excellent reactivity when polymerizing the binder polymer (P), it is preferable to use Celum (registered trademark) Ky Mixtia SA2400C as a polyrotaxane 10 comprising a cyclic molecule 1 having a cyclic skeleton composed of an α-cyclodextrin skeleton to which an acryloyl group as a group 4 containing an ethylenically unsaturated bond is bonded and a chain molecule 3 composed of polyethylene glycol having a number average molecular weight of 20,000 and having adamantyl groups as terminal groups 2 at both ends.
[0130] [Fourth structural unit]
[0131] The binder polymer (P) of the present embodiment may have a fourth structural unit as an optional structural unit. The fourth structural unit is derived from monomer (a4). Monomer (a4) is a compound having multiple independent ethylenically unsaturated bonds. The so-called "independent" means that it is not a conjugated double bond as that possessed by 1,3-butadiene. Therefore, monomer (a4) is a compound that can form a cross-linked structure in free radical polymerization with monomer (a1), monomer (a2) and monomer (a3). Monomer (a4) is not equivalent to any one of monomer (a1), monomer (a2) and monomer (a3). As monomer (a4), only one compound can be used, or two or more different compounds can be used.
[0132] Examples of the monomer (a4) include compounds having two ethylenically unsaturated bonds such as divinylbenzene, ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and 2-hydroxy-3-acryloxypropyl methacrylate, and compounds having three or more ethylenically unsaturated bonds such as trimethylolpropane tri(meth)acrylate. In order to obtain good polymerization stability when producing the binder polymer (P), the monomer (a4) is preferably at least one of divinylbenzene and trimethylolpropane triacrylate.
[0133] [Other monomers (a5)]
[0134] Other monomers (a5) are monomers that are not equivalent to any of monomers (a1), monomers (a2), monomers (a3), and monomers (a4). Examples of other monomers (a5) include compounds having only one ethylenically unsaturated bond and having anionic functional groups other than carboxyl groups such as sulfonic groups and phosphoric acid groups, surfactants having ethylenically unsaturated bonds (hereinafter sometimes referred to as "polymerizable surfactants"), and compounds having ethylenically unsaturated bonds and having a function as a silane coupling agent, but are not limited thereto.
[0135] Examples of the compound having only one ethylenically unsaturated bond and having a sulfonic group include aromatic vinyl compounds having a sulfonic group, aromatic vinyl compounds having a sulfonic group that forms a salt, and the like. Among them, at least one of p-styrenesulfonic acid and p-styrenesulfonate is preferably used, and p-styrenesulfonate is more preferably used. In order to obtain good polymerization stability when producing the binder polymer (P), sodium p-styrenesulfonate is further preferably used.
[0136] As the polymerizable surfactant which is an example of other monomer (a5), a compound having an ethylenically unsaturated bond and having a function as a surfactant can be used.
[0137] Examples of the polymerizable surfactant include compounds represented by the following chemical formulas (1) to (4).
[0138]
[0139] In formula (1), R 1 is an alkyl group. p is an integer from 10 to 40. 1 An alkyl group having 10 to 40 carbon atoms is preferred, and a linear unsubstituted alkyl group having 10 to 40 carbon atoms is more preferred.
[0140]
[0141] In formula (2), R 2 is an alkyl group. q is an integer of 10 to 12.2 It is preferably an alkyl group having 10 to 40 carbon atoms, and more preferably a linear unsubstituted alkyl group having 10 to 40 carbon atoms. Examples of the compound represented by formula (4) include polyoxyethylene alkyl ether sulfate (Aqualon KH-10, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.).
[0142]
[0143] In formula (3), R 3 M is an alkyl group. 1 is NH4 or Na. 3 An alkyl group having 10 to 40 carbon atoms is preferred, and a linear unsubstituted alkyl group having 10 to 40 carbon atoms is more preferred.
[0144]
[0145] In formula (4), R 4 M is an alkyl group. 2 is NH4 or Na. 4 An alkyl group having 10 to 40 carbon atoms is preferred, and a linear unsubstituted alkyl group having 10 to 40 carbon atoms is more preferred.
[0146] Examples of the compound having an ethylenically unsaturated bond and functioning as a silane coupling agent as an example of other monomer (a5) include vinyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, and γ-methacryloxypropyltriethoxysilane.
[0147] [Content ratio of each structural unit in the binder polymer (P)]
[0148] In the binder polymer (P) of the present embodiment, the content of each structural unit in the binder polymer (P) is regarded as being the same as the content of each monomer in the total amount of monomer components used to produce the binder polymer (P).
[0149] (Content ratio of the first structural unit in all structural units)
[0150] The content of the first structural unit in all structural units (in other words, the content of the monomer (a1) in the total amount of the monomer components used in the manufacture of the binder polymer (P)) is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 75% by mass or more, and particularly preferably 80% by mass or more. The reason is that better polymerization stability can be obtained when manufacturing the binder polymer (P). The content of the first structural unit in all structural units is preferably 97% by mass or less, more preferably 95% by mass or less, and further preferably 93% by mass or less. The reason is that it is a binder polymer (P) that can form an electrode in which the electrode active material layer is less likely to be peeled off from the collector.
[0151] Regarding the composition of the monomer (a1), it is preferred to appropriately adjust the type and amount of the compound in order to adjust the glass transition point of the binder polymer (P) or to adjust the polymerization rate in accordance with the molecular design.
[0152] Specifically, when the monomer (a1) contains an aromatic compound having an ethylenically unsaturated bond, the content of the structural unit derived from the aromatic compound having an ethylenically unsaturated bond in all structural units is preferably 36% by mass or more, more preferably 41% by mass or more, and further preferably 43% by mass or more. The reason is that when a non-aqueous secondary battery electrode slurry containing a binder polymer (P) is manufactured, the binder polymer (P) becomes excellent in dispersibility.
[0153] (Content ratio of the second structural unit in all structural units)
[0154] The content of the second structural unit in all structural units (in other words, the content of the monomer (a2) in the total amount of the monomer components used in the manufacture of the binder polymer (P)) is preferably 0.10% by mass or more, more preferably 1.0% by mass or more, further preferably 3.0% by mass, and particularly preferably 4.0% by mass or more. The reason is that an electrode in which the electrode active material layer is less likely to be peeled off from the collector can be formed. The content of the second structural unit in all structural units is preferably 20% by mass or less, more preferably 15% by mass or less, and further preferably 10% by mass or less. The reason is that better polymerization stability can be obtained when manufacturing the binder polymer (P). The content of the second structural unit in all structural units can be, for example, 2.0% by mass or more and 12% by mass or less, 5.0% by mass or more and 8% by mass or less, etc.
[0155] (Content ratio of the third structural unit in all structural units)
[0156] The content of the third structural unit in all structural units (in other words, the content of the monomer (a3) in the total amount of the monomer components used in the manufacture of the binder polymer (P)) is preferably 0.010 mass % or more, more preferably 0.050 mass % or more, and further preferably 0.10 mass % or more. The content of the third structural unit in all structural units can be 0.50 mass % or more, 1.0 mass % or more, 1.5 mass % or more, 2.0 mass % or more, 3.0 mass % or more, 3.5 mass % or more, 4.1 mass % or more, or 5.0 mass % or more. The reason is that by fully including the third structural unit in all structural units, the cross-linking density of the cyclic molecules 1 of the polyrotaxane 10 and the cross-linking density of the cyclic molecules 1 with the monomer (a1) and / or the monomer (a2) are sufficiently high, thereby forming a binder polymer (P) having excellent followability to the expansion and contraction of the electrode active material 22. Therefore, the binder polymer (P) containing 0.010 mass % or more of the third structural unit can be used as a binder material capable of forming an electrode 20 in which the electrode active material layer 24 is less likely to be separated from the current collector 23, thereby obtaining a non-aqueous secondary battery with better cycle characteristics.
[0157] The content of the third structural unit in all structural units is preferably 15% by mass or less, more preferably 12% by mass or less, further preferably 10% by mass or less, and particularly preferably 9.0% by mass or less. The reason is that it is easy to obtain a binder polymer (P) that fully contains the first structural unit and the second structural unit in all structural units.
[0158] (Content ratio of the fourth structural unit in all structural units)
[0159] In the case where the binder polymer (P) of the present embodiment includes the fourth structural unit, the content of the fourth structural unit in all structural units (in other words, the content of the monomer (a4) in the total amount of the monomer components used in the manufacture of the binder polymer (P)) is preferably 0.010 mass % or more, more preferably 0.020 mass % or more, and more preferably 0.030 mass % or more. The reason is that the effect of the internal cross-linking agent as the monomer (a4) can be significantly obtained, the degradation of the binder polymer (P) is suppressed, and the binder polymer (P) can be used as a material for a binder of a non-aqueous secondary battery with better cycle characteristics. The content of the fourth structural unit in all structural units is preferably 10 mass % or less, more preferably 5.0 mass % or less, further preferably 1.0 mass % or less, and particularly preferably 0.1 mass % or less. The reason is that the gelation of the binder polymer (P) can be suppressed. The content of the fourth structural unit in all structural units may be, for example, 0.015 mass % to 0.8 mass %, 0.025 mass % to 0.5 mass %, 0.035 mass % to 0.2 mass %, or 0.040 mass % to 0.080 mass %.
[0160] (Content ratio of the fifth structural unit in all structural units)
[0161] The adhesive polymer (P) of the present embodiment includes the fifth structural unit derived from other monomers (a5). When the other monomers (a5) are compounds having only one ethylenically unsaturated bond and a sulfonic group, the content of the fifth structural unit in all structural units (in other words, the content of the monomer (a5) in the total amount of the monomer components used in the manufacture of the adhesive polymer (P)) is preferably 0.10% by mass or more, more preferably 0.20% by mass or more, and further preferably 0.30% by mass or more. The reason is that good polymerization stability can be obtained when manufacturing the adhesive polymer (P). The content of the fifth structural unit in all structural units is preferably 5.0% by mass or less, more preferably 3.0% by mass or less, and further preferably 1.0% by mass or less. The reason is that the particle size, viscosity, etc. of the adhesive polymer (P) can be appropriately adjusted.
[0162] In the case where the binder polymer (P) of the present embodiment includes the fifth structural unit derived from other monomers (a5), and the other monomers (a5) are polymerizable surfactants, the content of the fifth structural unit in all structural units (in other words, the content of the monomer (a5) in the total amount of the monomer components used in the manufacture of the binder polymer (P)) is preferably 0.10% by mass or more, more preferably 0.20% by mass or more, and further preferably 0.30% by mass or more. The reason is that the effect brought about by the inclusion of the polymerizable surfactant becomes significant, and good polymerization stability can be obtained when manufacturing the binder polymer (P). The content of the fifth structural unit in all structural units is preferably 5.0% by mass or less, more preferably 3.0% by mass or less, and further preferably 1.0% by mass or less. The reason is that the particle size, viscosity, etc. of the binder polymer (P) can be appropriately adjusted. The content of the fifth structural unit in all structural units can be, for example, 0.50% by mass or more and 2.0% by mass or less, 0.80% by mass or more and 1.5% by mass or less, etc.
[0163] [Glass transition point Tg of binder polymer (P)]
[0164] The glass transition point Tg of the binder polymer (P) of the present embodiment is the peak top temperature of a DDSC chart obtained by DSC measurement using a differential scanning calorimetry (DSC) apparatus (EXSTAR DSC / SS7020 manufactured by Hitachi High-Tech Science & Technology Co., Ltd.) at a heating rate of 10°C / min in a nitrogen atmosphere and obtained as the temperature differential of DSC.
[0165] The glass transition point Tg of the binder polymer (P) is preferably -30°C or higher, more preferably -20°C or higher, and further preferably -10°C or higher. This is because a nonaqueous secondary battery having an electrode containing the binder for a nonaqueous secondary battery containing the binder polymer (P) has excellent cycle characteristics.
[0166] The glass transition point Tg of the binder polymer (P) is preferably 100° C. or less, more preferably 50° C. or less, and further preferably 40° C. or less. This is because the film-forming property of the binder polymer (P) is improved, and a non-aqueous secondary battery having an electrode including a binder for a non-aqueous secondary battery containing the binder polymer (P) has excellent cycle characteristics.
[0167] The glass transition point Tg of the binder polymer (P) may be, for example, -10 to 30°C, -5 to 25°C, or the like.
[0168] The number average molecular weight of the binder polymer (P) can be arbitrarily selected.
[0169] [Method for producing adhesive polymer (P)]
[0170] The adhesive polymer (P) of the present embodiment can be prepared, for example, by copolymerizing (polymerization step) monomers including monomers (a1), monomers (a2), monomers (a3), and, if necessary, monomers (a4) composed of compounds having multiple independent ethylenically unsaturated bonds, and / or other monomers (a5). The monomers (components of (a1) to (a5)) used to synthesize the adhesive polymer (P) are sometimes collectively referred to as monomers (a).
[0171] As a method for copolymerizing the monomer (a), for example, an emulsion polymerization method in which the monomer (a) is emulsion-polymerized in an aqueous medium (b) can be cited. When the binder polymer (P) is produced by the emulsion polymerization method, in addition to the monomer (a) and the aqueous medium (b), components such as a non-polymerizable surfactant (c), an alkaline substance (d), a free radical polymerization initiator (e), and a chain transfer agent (f) can also be used.
[0172] [Aqueous medium (b)]
[0173] The aqueous medium (b) is selected from water, a hydrophilic solvent, and a mixture of water and a hydrophilic solvent. As the hydrophilic solvent, methanol, ethanol, isopropanol, and N-methylpyrrolidone etc. can be mentioned. From the viewpoint of polymerization stability, the aqueous medium (b) is preferably water. As the aqueous medium (b), a mixture of a hydrophilic solvent added to water can be used as long as the polymerization stability is not impaired.
[0174] [Non-polymerizable surfactant (c)]
[0175] When the adhesive polymer (P) is manufactured by emulsion polymerization, a non-polymerizable surfactant (c) can be contained in a solution containing an aqueous medium (b) and a monomer (a) to perform emulsion polymerization. The so-called non-polymerizable surfactant (c) is a surfactant (c) that does not have a polymerizable unsaturated bond in its chemical structure. The surfactant (c) improves the dispersion stability of the solution in the emulsion polymerization and / or the dispersion (emulsion) obtained after the polymerization. As the surfactant (c), an anionic surfactant or a nonionic surfactant is preferably used.
[0176] Examples of the anionic surfactant include alkylbenzene sulfonates, alkyl sulfate ester salts, polyoxyethylene alkyl ether sulfate ester salts, and fatty acid salts.
[0177] Examples of the nonionic surfactant include polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene polycyclic phenyl ethers, polyoxyalkylene alkyl ethers, sorbitan fatty acid esters, and polyoxyethylene sorbitan fatty acid esters.
[0178] The surfactant (c) may be used alone or in combination of two or more.
[0179] [Alkaline substances (d)]
[0180] When the adhesive polymer (P) is manufactured by emulsion polymerization, an alkaline substance (d) may be added to the solution of the emulsion polymerization containing the aqueous medium (b) and the monomer (a), and / or the dispersion after the emulsion polymerization. By adding the alkaline substance (d), the acidic components contained in the monomer (a) are neutralized. As a result, the pH of the solution in the emulsion polymerization and / or the dispersion after the emulsion polymerization becomes an appropriate range, and the stability of the solution in the emulsion polymerization and / or the dispersion after the emulsion polymerization becomes good.
[0181] Examples of the alkaline substance (d) added to the solution for emulsion polymerization and / or the dispersion after emulsion polymerization include ammonia, triethylamine, sodium hydroxide, lithium hydroxide, etc. These alkaline substances (d) may be used alone or in combination of two or more.
[0182] [Free radical polymerization initiator (e)]
[0183] The radical polymerization initiator (e) used when producing the adhesive polymer (P) by emulsion polymerization is not particularly limited, and known substances can be used. Examples of the radical polymerization initiator (e) include persulfates such as ammonium persulfate and potassium persulfate; hydrogen peroxide; azo compounds; organic peroxides such as tert-butyl hydroperoxide, tert-butyl peroxybenzoate, and cumene hydroperoxide.
[0184] In the present embodiment, when the binder polymer (P) is produced by emulsion polymerization, redox polymerization may be performed using a reducing agent such as sodium hydrogen sulfite, Rongalite, or ascorbic acid together with a radical polymerization initiator (e).
[0185] The amount of free radical polymerization initiator (e) added (including the reducing agent in the case of using the reducing agent in combination) is preferably 0.001 parts by mass or more relative to 100 parts by mass of monomer (a), and more preferably 0.002 parts by mass or more. The reason is that when the binder polymer (P) is manufactured by emulsion polymerization, the conversion rate of monomer (a) to the binder polymer (P) can be high. The amount of free radical polymerization initiator (e) added is preferably 10 parts by mass or less relative to 100 parts by mass of monomer (a), and more preferably 5 parts by mass or less. The reason is that the molecular weight of the binder polymer (P) can be high, and the swelling rate of the non-aqueous secondary battery electrode containing the binder polymer (P) of the present embodiment relative to the electrolyte can be reduced. The above-mentioned amount, for example, relative to 100 parts by mass of monomer (a), can be 0.1 parts by mass or more and 4.0 parts by mass or less, 0.3 parts by mass or more and 3.0 parts by mass or less, 0.5 parts by mass or more and 2.5 parts by mass or less, 1.0 parts by mass or more and 2.0 parts by mass or less, etc.
[0186] [Chain transfer agent (f)]
[0187] The chain transfer agent (f) used when producing the binder polymer (P) by emulsion polymerization is used to adjust the molecular weight of the binder polymer (P) obtained by emulsion polymerization. Examples of the chain transfer agent (f) include n-dodecyl mercaptan, tert-dodecyl mercaptan, n-butyl mercaptan, 2-ethylhexyl mercaptoacetate, 2-mercaptoethanol, β-mercaptopropionic acid, methanol, n-propanol, isopropanol, tert-butyl alcohol, benzyl alcohol, and the like.
[0188] [Emulsion polymerization method]
[0189] As the emulsion polymerization method used when manufacturing the binder polymer (P), for example, there can be mentioned a method of carrying out emulsion polymerization while continuously supplying each component used for emulsion polymerization into a reaction container. The temperature of the emulsion polymerization is not particularly limited, and is, for example, 30 to 90° C., preferably 50 to 85° C., and more preferably 55 to 80° C. The emulsion polymerization is preferably carried out while stirring. In addition, it is preferred that the monomer (a) and the free radical polymerization initiator (e) are continuously supplied to the solution in the emulsion polymerization in such a manner that the concentrations of the monomer (a) and the free radical polymerization initiator (e) in the solution in the emulsion polymerization become uniform.
[0190] <2. Binders for non-aqueous secondary batteries>
[0191] The non-aqueous secondary battery binder of the present embodiment includes the binder polymer (P) of the present embodiment. The electrode binder for non-aqueous secondary batteries may include other components together with the binder polymer (P). Specifically, the electrode binder for non-aqueous secondary batteries may include, for example, polymers other than the binder polymer (P), surfactants, etc.
[0192] The binder for non-aqueous secondary batteries is composed of components that do not volatilize and remain even when a heating process is performed in the manufacturing method of the non-aqueous secondary battery described later. Specifically, the components constituting the binder for non-aqueous secondary batteries are components that remain after weighing 1 g of a binder composition for non-aqueous secondary batteries containing a binder polymer (P), placing it on an aluminum dish with a diameter of 5 cm and placing it in a dryer, and drying it at 1 atmosphere (1013 hPa) and a temperature of 105°C for 1 hour while circulating the air in the dryer.
[0193] The content of the binder polymer (P) contained in the binder for non-aqueous secondary batteries is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and further preferably 98% by mass or more. This is because the effect brought about by the inclusion of the binder polymer (P) becomes significant.
[0194] <3. Binder composition for non-aqueous secondary batteries>
[0195] The binder composition for non-aqueous secondary batteries of the present embodiment comprises dispersed particles containing the binder polymer (P) of the present embodiment and an aqueous medium (B). The binder composition for non-aqueous secondary batteries of the present embodiment preferably comprises dispersed particles of the binder polymer (P) dispersed in an emulsion state in an aqueous medium (B). As dispersed particles, for example, emulsified particles comprising a binder polymer (P) and a surfactant, particles comprising a binder polymer (P) having a structural unit derived from a polymerizable surfactant, and the like can be cited.
[0196] The binder composition for non-aqueous secondary batteries may contain other components together with the binder polymer (P) and the aqueous medium (B). Specifically, the binder composition for non-aqueous secondary batteries may contain, for example, the above-mentioned components used for the synthesis of the binder polymer (P).
[0197] The binder composition for non-aqueous secondary batteries of the present embodiment may be a dispersion obtained by manufacturing a binder polymer (P) by emulsion polymerization. That is, the binder composition for non-aqueous secondary batteries may be an emulsion comprising a binder polymer (P) and an aqueous medium (B). In addition, the binder composition for non-aqueous secondary batteries of the present embodiment may be a dispersion obtained by dispersing a binder polymer (P) obtained by a method other than emulsion polymerization in an aqueous medium (B). In this case, as a method for dispersing a binder polymer (P) in an aqueous medium (B), a known method may be used.
[0198] [Average particle size d50 of dispersed particles containing the binder polymer (P)]
[0199] The average particle size d50 of the dispersed particles containing the binder polymer (P) in the binder composition for non-aqueous secondary batteries of the present embodiment is preferably 0.18 μm or more, and more preferably 0.20 μm or more. The reason is that if the average particle size d50 is 0.18 μm or more, an electrode in which the electrode active material layer is less likely to be peeled off from the current collector can be formed.
[0200] The average particle size d50 of the dispersed particles containing the binder polymer (P) in the binder composition for non-aqueous secondary batteries of the present embodiment is preferably 1.0 μm or less, more preferably 0.80 μm or less, further preferably 0.60 μm or less, and particularly preferably 0.50 μm or less. If the average particle size d50 in the binder polymer (P) is 1.0 μm or less, when the electrode sheet having the electrode active material layer 24 formed on the collector 23 is pressed in order to manufacture an electrode containing the binder polymer (P), it can be pressed under suitable pressing conditions. As a result, the electrode active material 24 can be more firmly bonded to the collector 23.
[0201] The average particle size d50 of the dispersed particles containing the binder polymer (P) in the binder composition for non-aqueous secondary batteries of the present embodiment can be adjusted by a known method. For example, it can be adjusted by the amount of surfactant added when the binder polymer (P) is manufactured by emulsion polymerization, the selection of monomers, etc. The average particle size d50 of the dispersed particles can be measured, for example, by using a dynamic light scattering method (DLS) using a microtrac.
[0202] 〔Aqueous medium (B)〕
[0203] The aqueous medium (B) in the binder composition for non-aqueous secondary batteries of the present embodiment is water, a hydrophilic solvent, or a mixture thereof. As the hydrophilic solvent, the same substance as the hydrophilic solvent exemplified as the aqueous medium (b) used in the synthesis of the binder polymer (P) can be cited. The aqueous medium (B) and the aqueous medium (b) used in the synthesis of the binder polymer (P) may be the same or different.
[0204] In the case where the binder composition for non-aqueous secondary batteries is an emulsion obtained by manufacturing a binder polymer (P) by emulsion polymerization, the aqueous medium (B) may be an aqueous medium (b) used for the synthesis of the binder polymer (P). In addition, the aqueous medium (B) may also be a substance in which a new aqueous medium is added to the aqueous medium (b) used for the synthesis of the binder polymer (P). In addition, the aqueous medium (B) may also be a substance in which a part or all of the aqueous medium (b) contained in the dispersion obtained by manufacturing a binder polymer (P) by emulsion polymerization is replaced with a new aqueous solvent. The new aqueous medium used in this case may be the same composition as the aqueous medium (b) used for the synthesis of the binder polymer (P) or a different composition.
[0205] [Non-volatile content concentration of the binder composition for non-aqueous secondary batteries]
[0206] The non-volatile component concentration of the binder composition for non-aqueous secondary batteries of the present embodiment is preferably 20% by mass or more, more preferably 25% by mass or more, and further preferably 30% by mass or more. The reason is that the amount of active ingredients contained in the binder composition for non-aqueous secondary batteries is large. The non-volatile component concentration of the binder composition for non-aqueous secondary batteries can be adjusted by the content of the aqueous medium (B) contained in the binder composition for non-aqueous secondary batteries.
[0207] The non-volatile content of the binder composition for non-aqueous secondary batteries is preferably 80% by mass or less, more preferably 70% by mass or less, and further preferably 60% by mass or less. The reason is that the increase in viscosity of the binder composition for non-aqueous secondary batteries is suppressed, and the slurry for non-aqueous secondary battery electrodes is easy to prepare.
[0208] <4. Slurry for non-aqueous secondary battery electrodes>
[0209] Next, the non-aqueous secondary battery electrode slurry of the present embodiment is described in detail. The non-aqueous secondary battery electrode slurry comprises a binder polymer (P) of the present embodiment, an electrode active material, and an aqueous medium. The binder polymer (P) and the electrode active material contained in the non-aqueous secondary battery electrode slurry are preferably dispersed in an aqueous medium. In addition to the binder polymer (P), the electrode active material, and the aqueous medium, the non-aqueous secondary battery electrode slurry may also include a thickener, a conductive aid, the above-mentioned components used in the synthesis of the binder polymer (P), etc.
[0210] [Content of Binder Polymer (P)]
[0211] The content of the binder polymer (P) contained in the non-aqueous secondary battery electrode slurry is preferably 0.50 parts by mass or more, more preferably 1.0 parts by mass or more, based on 100 parts by mass of the electrode active material, in order to fully demonstrate the effect of containing the binder polymer (P).
[0212] The content of the binder polymer (P) contained in the non-aqueous secondary battery electrode slurry is preferably 5.0 parts by mass or less, more preferably 4.0 parts by mass or less, and further preferably 3.0 parts by mass or less relative to 100 parts by mass of the electrode active material. The reason is that the content of the electrode active material contained in the non-aqueous secondary battery electrode slurry can be increased.
[0213] 〔Electrode active material〕
[0214] The electrode active material contained in the non-aqueous secondary battery electrode slurry is a material capable of intercalating / deintercalating ions such as lithium ions that serve as charge carriers. The ions that serve as charge carriers are preferably alkali metal ions, more preferably lithium ions, sodium ions, potassium ions, and even more preferably lithium ions.
[0215] In the case where the non-aqueous secondary battery electrode manufactured using the non-aqueous secondary battery electrode slurry is a negative electrode, the electrode active material is a negative electrode active material. As the negative electrode active material, it is preferred to contain at least one of a carbon material, a material containing silicon, and a material containing titanium. As a carbon material used as a negative electrode active material, for example, coke such as petroleum coke, asphalt coke, coal coke, carbide of organic polymers, graphite such as artificial graphite, and natural graphite can be cited. As a material containing silicon used as a negative electrode active material, for example, silicon compounds such as silicon simple substance and silicon oxide can be cited. As a material containing titanium used as a negative electrode active material, for example, lithium titanate can be cited. These materials used as negative electrode active materials can be used alone or mixed or composited.
[0216] The negative electrode active material preferably contains at least one of a carbon material and a silicon-containing material, and more preferably contains a carbon material. The reason is that the binder polymer (P) contained in the non-aqueous secondary battery electrode slurry has a great effect of improving the bonding between the negative electrode active materials and between the negative electrode active materials and the collector.
[0217] In the case where the non-aqueous secondary battery electrode manufactured using the non-aqueous secondary battery electrode slurry is a positive electrode, the electrode active material is a positive electrode active material. As a positive electrode active material, a material having a higher standard electrode potential than the negative electrode active material is used. Specifically, as a positive electrode active material, lithium composite oxides including nickel, lithium cobalt oxide (LiCoO2), spinel lithium manganese oxide (LiMn2O4), olivine lithium iron phosphate, TiS2, MnO2, MoO3, V2O5 and other chalcogen compounds can be cited, etc. These materials used as positive electrode active materials can be used alone or in combination of two or more.
[0218] 〔Aqueous medium〕
[0219] The aqueous medium contained in the non-aqueous secondary battery electrode slurry of the present embodiment is one selected from water, a hydrophilic solvent, and a mixture of water and a hydrophilic solvent. As the hydrophilic solvent, the same substance as the hydrophilic solvent exemplified as the aqueous medium (b) used in the synthesis of the binder polymer (P) can be cited. The aqueous medium contained in the non-aqueous secondary battery electrode slurry and the aqueous medium (b) used in the synthesis of the binder polymer (P) may be the same or different.
[0220] 〔Thickener〕
[0221] As thickeners that can be included in the non-aqueous secondary battery electrode slurry, celluloses such as carboxymethyl cellulose (CMC), hydroxyethyl cellulose, hydroxypropyl cellulose, ammonium salts of celluloses, alkali metal salts of celluloses, polyvinyl alcohol, polyvinyl pyrrolidone, etc. can be cited. The thickener preferably includes at least one of carboxymethyl cellulose, ammonium salts of carboxymethyl cellulose, and alkali metal salts of carboxymethyl cellulose. The reason is that the electrode active material in the non-aqueous secondary battery electrode slurry is easy to disperse.
[0222] The content of the thickener contained in the non-aqueous secondary battery electrode slurry is preferably 0.50 parts by mass or more relative to 100 parts by mass of the electrode active material, and more preferably 0.80 parts by mass or more. The reason is that the adhesion between the electrode active materials contained in the non-aqueous secondary battery electrode produced using the non-aqueous secondary battery electrode slurry and between the electrode active material and the collector becomes good. The content of the thickener contained in the non-aqueous secondary battery electrode slurry is preferably 3.0 parts by mass or less relative to 100 parts by mass of the electrode active material, more preferably 2.0 parts by mass or less, and further preferably 1.5 parts by mass or less. The reason is that the coating property of the non-aqueous secondary battery electrode slurry becomes good.
[0223] 〔Conductive additive〕
[0224] As the conductive auxiliary agent that can be included in the non-aqueous secondary battery electrode slurry of the present embodiment, carbon black, carbon fiber, etc. can be cited. As carbon black, furnace black, acetylene black, DENKA BLACK (registered trademark) (DENKA Co., Ltd.), CHECKEN BLACK (registered trademark) (CHECKEN BLACK INTARSIONAL Co., Ltd.), etc. can be cited. As carbon fiber, carbon nanotubes, carbon nanofibers, etc. can be cited. As carbon nanotubes, VGCF (registered trademark, Showa Denko Co., Ltd.) as vapor-grown carbon fiber can be cited as a preferred example.
[0225] [Method for producing slurry for non-aqueous secondary battery electrodes]
[0226] As a method for manufacturing the non-aqueous secondary battery electrode slurry of the present embodiment, for example, the binder polymer (P) of the present embodiment, the electrode active material, the aqueous medium, the thickener contained as needed, the conductive aid contained as needed, and the other components contained as needed are mixed. The mixing order of the components as the raw materials of the non-aqueous secondary battery electrode slurry is not particularly limited and can be appropriately determined. As a method for mixing the components, a method using a mixing device such as a stirring type, a rotating type, and an oscillating type can be cited.
[0227] <5. Non-aqueous secondary battery electrodes>
[0228] Next, the non-aqueous secondary battery electrode of this embodiment is described in detail. The electrode of this embodiment includes the binder polymer (P) of this embodiment. Figure 1 As shown, the electrode 20 of the present embodiment includes a current collector 23 and an electrode active material layer 24 formed on the current collector 23. Examples of the shape of the electrode 20 of the present embodiment include a laminate and a wound body, but are not particularly limited.
[0229] The formation range of the electrode active material layer 24 on the current collector 23 is not particularly limited, and the electrode active material layer 24 may be formed on the entire surface of the current collector 23, or may be formed on only a portion of the surface of the current collector 23. When the current collector 23 is in the shape of a plate, foil, etc., the electrode active material layer 24 may be formed on both surfaces of the current collector 23, or may be formed on only one surface.
[0230] 〔Current Collector〕
[0231] The collector 23 is preferably a metal sheet having a thickness of 0.001 mm or more and 0.5 mm or less. Examples of the metal forming the metal sheet include iron, copper, aluminum, nickel, stainless steel, etc. When the electrode 20 of the present embodiment is a negative electrode of a lithium ion secondary battery, the collector 23 is preferably a copper foil.
[0232] [Electrode active material layer]
[0233] The electrode active material layer 24 contains the binder polymer (P) of this embodiment (in Figure 1 The electrode active material layer 24 may also contain a conductive additive, a thickener, etc. The electrode active material 22, the conductive additive, and the thickener may be the same as those exemplified as the components of the slurry for non-aqueous secondary battery electrodes.
[0234] [Method for producing non-aqueous secondary battery electrode]
[0235] The electrode 20 of the present embodiment can be manufactured, for example, by the method shown below. First, the non-aqueous secondary battery electrode slurry of the present embodiment is applied to the collector 23. Then, the non-aqueous secondary battery electrode slurry is dried. Thus, an electrode active material layer 24 containing a binder polymer (P) is formed on the collector 23 to prepare an electrode sheet. Then, the electrode sheet is cut into an appropriate size as needed. By performing the above steps, the electrode 20 of the present embodiment is obtained.
[0236] As a method for coating the non-aqueous secondary battery electrode slurry on the collector 23, there is no particular limitation, and examples thereof include a reverse roll method, a direct roll method, a doctor blade method, a knife method, an extrusion method, a curtain method, a gravure method, a rod method, an immersion method, an extrusion method, etc. Among these coating methods, if various physical properties and dryness of the non-aqueous secondary battery electrode slurry such as viscosity are considered, it is preferred to use any method selected from the direct roll method, the doctor blade method, the knife method, or the extrusion method. The reason is to obtain an electrode active material layer with a smooth surface and a small deviation in thickness.
[0237] When the nonaqueous secondary battery electrode slurry is applied to both surfaces of the current collector 23, it may be applied sequentially or simultaneously. The nonaqueous secondary battery electrode slurry may be applied to the current collector 23 continuously or intermittently.
[0238] The coating amount of the nonaqueous secondary battery electrode slurry can be appropriately determined according to the design capacity of the battery 20 , the composition of the nonaqueous secondary battery electrode slurry, and the like.
[0239] The method for drying the nonaqueous secondary battery electrode slurry applied on the current collector 23 is not particularly limited, and for example, methods selected from hot air, reduced pressure or vacuum environment, (far) infrared rays, and low-temperature air can be used alone or in combination.
[0240] The drying temperature and drying time when drying the non-aqueous secondary battery electrode slurry can be appropriately adjusted according to the concentration of the non-volatile component in the non-aqueous secondary battery electrode slurry, the coating amount on the collector 23, etc. The drying temperature is preferably 40° C. to 350° C., and more preferably 60° C. to 100° C. from the viewpoint of productivity. The drying time is preferably 1 minute to 30 minutes.
[0241] The electrode sheet having the electrode active material layer 24 formed on the current collector 23 can be cut into a size and shape suitable for the electrode 20. The electrode sheet can be cut by any method, such as slit, laser, wire cutting, cutter, Thomson, etc.
[0242] In this embodiment, the electrode sheet may be pressed as needed before or after it is cut, so that the electrode active material 24 can be more firmly bonded to the collector 23 and the thickness of the electrode 20 can be reduced, thereby miniaturizing the non-aqueous secondary battery.
[0243] As a method for pressing the electrode sheet, a general method can be used. As a pressing method, a die pressing method or a roll pressing method is particularly preferably used.
[0244] When using the die pressing method, the pressing pressure is not particularly limited, but is preferably 0.5 t / cm 2 Above and 5t / cm 2 the following.
[0245] When the roller pressing method is used, the pressing load is not particularly limited, but is preferably 0.5 t / cm or more and 8 t / cm or less. The reason is to obtain the above-mentioned effect brought about by pressing and to suppress the reduction of the insertion and extraction capacity of charge carriers such as lithium ions into the electrode active material.
[0246] <6. Non-aqueous secondary batteries>
[0247] Next, a lithium ion secondary battery will be described as a preferred example of the nonaqueous secondary battery according to the present embodiment. The configuration of the nonaqueous secondary battery of the present invention is not limited to the example described below.
[0248] The lithium ion secondary battery of the present embodiment is a battery in which known components such as a positive electrode, a negative electrode, an electrolyte solution, and a separator provided as necessary are accommodated in an outer casing.
[0249] The shape of the lithium ion secondary battery may be any shape such as a coin shape, a button shape, a sheet shape, a cylinder shape, a square shape, or a flat shape.
[0250] 〔Positive electrode / Negative electrode〕
[0251] One or both of the positive electrode and the negative electrode of the lithium ion secondary battery of this embodiment include the electrode active material layer of this embodiment containing the binder polymer (P) of this embodiment. In the lithium ion secondary battery of this embodiment, at least the negative electrode of the positive electrode and the negative electrode preferably includes the electrode active material layer containing the binder polymer (P).
[0252] In the case where only one of the positive and negative electrodes of the lithium ion secondary battery of the present embodiment has an electrode active material layer containing the binder polymer (P) of the present embodiment, as an electrode not containing the binder polymer (P) of the present embodiment, a substance containing a known binder such as polyvinylidene fluoride can be used instead of the binder polymer (P) of the present embodiment.
[0253] 〔Electrolyte〕
[0254] As the electrolyte, a non-aqueous liquid having ion conductivity is used. As the electrolyte, a solution in which an electrolyte is dissolved in an organic solvent, an ionic liquid, etc. can be cited, and the former is preferred. The reason is to obtain a lithium ion secondary battery with low manufacturing cost and low internal resistance.
[0255] As the electrolyte, an alkali metal salt can be used, and it can be appropriately selected according to the type of electrode active material. Examples of the electrolyte include LiClO4, LiBF6, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiB 10 Cl 10 , LiAlCl4, LiCl, LiBr, LiB(C2H5)4, CF3SO3Li, CH3SO3Li, LiCF3SO3, LiC4F9SO3, Li(CF3SO2)2N, aliphatic lithium carboxylate, etc. In addition, other alkali metal salts can also be used as the electrolyte.
[0256] As the organic solvent of dissolving electrolyte, it is not particularly limited, for example, can enumerate, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), fluoroethylene carbonate (FEC), carboxylic acid esters such as nitrile compounds such as vinyl carbonate (VC), acetonitrile, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate. These organic solvents can be used alone 1 kind, also can be used in combination of 2 or more. Among them, as organic solvent, preferably use the material of the straight chain carbonate solvent combined.
[0257] [Exterior body]
[0258] As the outer casing, for example, one formed of an aluminum laminate composed of an aluminum foil and a resin film can be appropriately used, but the outer casing is not limited thereto.
[0259] Example
[0260] The present invention will be specifically described below by way of examples and comparative examples. In addition, the examples shown below are intended to facilitate understanding of the contents of the present invention. The present invention is not limited to these examples.
[0261] In the following examples, a negative electrode of a lithium ion secondary battery is prepared as an example of a non-aqueous secondary battery electrode of the present invention, and a lithium ion secondary battery is prepared as an example of a non-aqueous secondary battery, and the negative electrode of the lithium ion secondary battery and the lithium ion secondary battery involved in the comparative example are compared to confirm the effect of the present invention.
[0262] In addition, water used in the following Examples and Comparative Examples is ion-exchanged water unless otherwise specified.
[0263] <1. Production of Binder Polymer>
[0264] In each of the Examples and Comparative Examples, monomer (a) in the amount shown in Tables 1 to 3 was mixed with 200 parts by mass of water as an aqueous medium (b) and emulsified to prepare a monomer emulsion. In this example, (a5) contained a polymerizable surfactant.
[0265] Next, aqueous solutions were prepared by dissolving the radical polymerization initiator (e) in the amounts shown in Tables 1 to 3 in 50 parts by mass of water.
[0266] 150 parts by mass of water were added to a separable flask equipped with a cooling tube, a thermometer, a stirrer, and a dropping funnel, and the temperature was raised to 80° C. In the separable flask, the monomer emulsion and the aqueous solution in which the radical polymerization initiator (e) was dissolved were continuously supplied while stirring at 80° C. for 3 hours, respectively, to carry out emulsion polymerization, and an emulsion containing dispersed particles of the binder polymers of Examples 1 to 11 and Comparative Examples 1 to 2 and an aqueous medium was obtained.
[0267] The obtained emulsion was cooled to room temperature. Then, 133 parts by mass of water and 25% by mass of aqueous ammonia were added. Thus, a non-aqueous secondary battery binder composition of Examples 1 to 11 and Comparative Examples 1 to 2, which was composed of an emulsion containing dispersed particles of the binder polymer of Examples 1 to 11 and Comparative Examples 1 to 2 dispersed in an aqueous medium, was prepared.
[0268] [Table 1]
[0269]
[0270] ※1: The values on the right column of the monomers are the mass % of each monomer.
[0271] [Table 2]
[0272]
[0273] ※1: The values on the right column of the monomers are the mass % of each monomer.
[0274] [Table 3]
[0275]
[0276] ※1: The values on the right column of the monomers are the mass % of each monomer.
[0277] The amount of ammonia as the alkaline substance (d) shown in Tables 1 to 3 is the amount of ammonia contained in aqueous ammonia (parts by mass).
[0278] The amount of water as the aqueous medium (b) shown in Tables 1 to 3 is the total amount (parts by mass) of water contained in the binder composition for a non-aqueous secondary battery.
[0279] The polyrotaxane (SA2400C) in the monomer (a3) shown in Tables 1 to 3 is Celum (registered trademark) Key Microstar SA2400C (manufactured by Artband Soft Materials Co., Ltd.), which is a polyrotaxane containing a cyclic molecule and a chain molecule, wherein the cyclic molecule has a cyclic skeleton composed of α-cyclodextrin to which an acryloyl group is bonded, and the chain molecule is composed of polyethylene glycol having a number average molecular weight of 20,000 having adamantyl groups at both ends.
[0280] The monomer (a5) is a polyoxyethylene alkyl ether sulfate salt (Aqualon KH-10, manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.) as a polymerizable surfactant.
[0281] Rongalite SFS in the polymerization initiator (e) is a trade name of Rongalite manufactured by Sumitomo Seika Chemicals, Ltd.
[0282] <2. Evaluation of Binder Polymer and Binder Composition for Non-aqueous Secondary Batteries>
[0283] The glass transition point (Tg) and particle size (d50) of the binder polymers of Examples 1 to 11 and Comparative Examples 1 and 2 were measured by the following methods. The results are shown in Tables 1 to 3.
[0284] In addition, the non-volatile content of the binder compositions for non-aqueous secondary batteries of Examples 1 to 11 and Comparative Examples 1 and 2 was measured by the following method.
[0285] 〔Glass transition point Tg〕
[0286] The binder composition for a non-aqueous secondary battery was applied onto a release PET (polyethylene terephthalate) film and dried at 50° C. for 5 hours to obtain a 2 mm thick film made of a binder polymer.
[0287] A square test piece of 2 mm in length and 2 mm in width was cut out from the obtained film. The test piece was sealed in an aluminum pan, and a differential scanning calorimeter (EXSTAR DSC / SS7020 manufactured by Hitachi High Tech Science Co., Ltd.) was used to measure the differential scanning calorimetry (DSC) of the test piece under a nitrogen atmosphere at a heating rate of 10°C / min. The temperature range of the DSC measurement was set to -40°C to 200°C. Furthermore, the peak temperature of the DDSC graph obtained as the temperature differential of the DSC was measured, and the temperature was set as the glass transition point Tg (°C) of the binder polymer.
[0288] [Particle size (d50) of dispersed particles containing a binder polymer]
[0289] The particle size of the binder composition for a non-aqueous secondary battery was measured by a dynamic light scattering method (DLS) at room temperature using NANOTORAC WAVE II (manufactured by Microtrac Bell Co., Ltd.) to obtain a particle size (d50) of the binder polymer.
[0290] 〔Non-volatile content concentration〕
[0291] 1 g of the binder composition for non-aqueous secondary batteries was weighed, placed on an aluminum dish with a diameter of 5 cm, and placed in a dryer. The mixture was dried at 1 atmosphere (1013 hPa) and 105°C for 1 hour while circulating the air in the dryer, and the mass of the remaining components was measured. The ratio (mass %) of the mass of the above-mentioned components remaining after drying relative to the mass (1 g) of the binder composition for non-aqueous secondary batteries before drying was calculated and set as the non-volatile component concentration (mass %).
[0292] <3. Production of non-aqueous secondary batteries>
[0293] A negative electrode was prepared by the method described below using the binder composition for nonaqueous secondary batteries of Examples 1 to 11 and Comparative Examples 1 to 2, and a lithium ion secondary battery was prepared as the nonaqueous secondary battery of Examples 1 to 11 and Comparative Examples 1 to 2 using the negative electrode.
[0294] [Production of positive electrode]
[0295] LiNi as the positive electrode active material 0.6 Mn0.2 Co 0.2 94 parts by mass of O2, 3 parts by mass of acetylene black as a conductive aid, and 3 parts by mass of polyvinylidene fluoride as a binder were mixed to obtain a mixture. 50 parts by mass of N-methylpyrrolidone was added to the obtained mixture and further mixed to obtain a positive electrode slurry.
[0296] As a positive electrode current collector, an aluminum foil with a thickness of 15 μm was prepared. The positive electrode slurry was applied to both sides of the positive electrode current collector by direct roll method. The amount of positive electrode slurry applied to the positive electrode current collector was adjusted so that the thickness after roll pressing treatment described later would be 125 μm per side.
[0297] The positive electrode slurry coated on the positive electrode collector was dried at 120°C for 5 minutes and pressed by a roll press (manufactured by Suntech Metal, with a pressing load of 5 t / cm and a roll width of 7 cm) to obtain a positive electrode sheet having a positive electrode active material layer on both sides of the positive electrode collector. The obtained positive electrode sheet was cut into a rectangle of 50 mm in length and 40 mm in width, and a conductive sheet was connected to serve as a positive electrode.
[0298] [Production of negative electrode (non-aqueous secondary battery electrode)]
[0299] 96.9 parts by mass of artificial graphite (G49, manufactured by Jiangxi Zichen Technology Co., Ltd.) as a negative electrode active material, 3.6 parts by mass of any non-aqueous secondary battery binder composition prepared in Examples 1 to 11 and Comparative Examples 1 to 2 (1.4 parts by mass of non-volatile components (binder polymer)), and 60 parts by mass of a 2% aqueous solution of CMC (carboxymethylcellulose-sodium salt, manufactured by Nippon Paper Chemical Co., Ltd., Sunlouse (registered trademark) MAC500LC) were mixed, and 16 parts by mass of water were further added, and mixed using a rotation-revolution mixer (ARE-310, manufactured by Shinkyo Co., Ltd.) to obtain a negative electrode slurry (slurry for non-aqueous secondary battery electrodes).
[0300] A copper foil with a thickness of 10 μm was prepared as a negative electrode current collector. The negative electrode slurry was applied to both sides of the negative electrode current collector by direct roll method. The amount of negative electrode slurry applied to the negative electrode current collector was adjusted so that the thickness after roll pressing treatment described later would be 170 μm per side.
[0301] The negative electrode slurry coated on the negative electrode collector was dried at 90°C for 10 minutes and pressed by a roll pressing method using a roll press (manufactured by Suntech Metal, with a pressing load of 8 t / cm and a roll width of 7 cm) to obtain a negative electrode sheet having a negative electrode active material layer on both sides of the negative electrode collector. The obtained negative electrode sheet was cut into a rectangle of 52 mm in length and 42 mm in width, and a conductive sheet was connected to serve as a negative electrode.
[0302] [Production of non-aqueous secondary batteries]
[0303] A separator (made of polyethylene, 25 μm thick) composed of a porous film of a polyolefin system is placed between the positive electrode and the negative electrode, and the positive electrode active material layer and the negative electrode active material layer are stacked in a manner opposite to each other, and are housed in an outer body (battery pack) composed of an aluminum laminate. Then, an electrolyte is injected into the outer body, vacuum impregnation is performed, and packaging is performed using a vacuum heat sealer to obtain a lithium ion secondary battery.
[0304] As the electrolyte, a substance obtained by mixing 99 parts by mass of a solution obtained by dissolving LiPF6 at a concentration of 1.0 mol / L in a mixed solvent containing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in a volume ratio of EC:EMC:DEC=30:50:20 and 1 part by mass of vinylene carbonate was used.
[0305] <4. Evaluation of non-aqueous secondary batteries>
[0306] The internal resistance and the discharge capacity retention rate after 500 cycles of the lithium ion secondary batteries of Examples 1 to 11 and Comparative Examples 1 and 2 were evaluated by the following methods. The results are shown in Tables 1 to 3.
[0307] 〔Internal resistance (DCR)〕
[0308] The internal resistance (DCR (Ω)) of the lithium-ion secondary battery was measured at 25°C by the following steps. That is, constant current charging was performed at 0.2C from the static potential until the voltage reached 3.6V, so that the charging state was 50% of the initial capacity (SOC50%). Then, discharge was performed for 60 seconds at current values of 0.2C, 0.5C, 1C, and 2C. The internal resistance DCR (Ω) at SOC50% was determined from the relationship between these four current values (values for 1 second) and voltage.
[0309] [Discharge capacity maintenance rate after 500 cycles]
[0310] Under the condition of 45°C, a series of operations of steps (i) to (iv) shown below were performed once as one cycle, and charge and discharge were performed. The time integral value of the current in steps (i) and (ii) was set as the charge capacity, and the time integral value of the current in step (iv) was set as the discharge capacity. Furthermore, the discharge capacity of the first cycle and the discharge capacity of the 500th cycle were measured, and the discharge capacity maintenance rate after 500 cycles was calculated by the following formula.
[0311] Discharge capacity retention rate (%) = 100 × (discharge capacity at the 500th cycle / discharge capacity at the 1st cycle)
[0312] (i) The battery is charged at a current of 1 C until the voltage reaches 4.2 V (constant current (CC) charging).
[0313] (ii) Charging was performed at a voltage of 4.2 V until the current reached 0.05 C (constant voltage (CV) charging).
[0314] (iii) Allow to stand for 30 minutes.
[0315] (iv) Discharging at a current of 1 C until the voltage reaches 2.75 V (constant current (CC) discharge).
[0316] <5. Evaluation results>
[0317] As shown in Tables 1 to 3, it was confirmed that the capacity retention rate of the lithium ion secondary batteries of Examples 1 to 11 was higher than that of the lithium ion secondary batteries of Comparative Examples 1 to 2. This is presumably because the binder polymer included in the negative electrode of the lithium ion secondary batteries of Examples 1 to 11 is a copolymer including structural units derived from monomers (a1) to (a3) shown in Tables 1 to 3.
[0318] In particular, the capacity retention rate of the lithium ion secondary battery of Example 5 was 90%, and the cycle characteristics were very excellent. This is presumably because the content of the monomer (a3) in the total amount of the monomer (a) of the binder polymer contained in the negative electrode of the lithium ion secondary battery of Example 5 (the content of the third structural unit in all structural units) was 4.1% by mass or more.
[0319] Furthermore, as shown in Tables 1 to 3, it was confirmed that the lithium ion secondary batteries of Examples 1 to 11 and Comparative Examples 1 and 2 had sufficiently low values for practical use from the viewpoint of internal resistance, which is a secondary effect.
[0320] Industrial Availability
[0321] The present invention provides a binder polymer for a non-aqueous secondary battery that can be used as a material for forming a binder for an electrode of a non-aqueous secondary battery that can provide excellent cycle characteristics.
[0322] Explanation of symbols
[0323] 1···Cyclic molecules
[0324] 2···Terminal group
[0325] 3···Chain molecules
[0326] 4···Groups containing ethylenically unsaturated bonds
[0327] 10···Polyrotaxane
[0328] 11···Opening
[0329] 20···Electrode
[0330] 21. Thickener
[0331] 22···Electrode active material
[0332] 23···Current Collector
[0333] 24···Electrode active material layer
[0334] 25···Adhesive.
Claims
1. A binder polymer for a non-aqueous secondary battery, characterized in that: have: The first structural unit derived from monomer a1; a second structural unit derived from monomer a2; and The third structural unit derived from monomer a3, The monomer a1 is a nonionic compound having only one ethylenically unsaturated bond. The monomer a2 is a compound having a carboxyl group and only one ethylenically unsaturated bond, The monomer a3 is a polyrotaxane having a cyclic molecule and a chain molecule, wherein the cyclic molecule has a cyclic skeleton to which a group containing an ethylenically unsaturated bond is bonded, and the chain molecule penetrates the opening of the cyclic molecule and has end-capping groups at both ends. 2 . The binder polymer for a nonaqueous secondary battery according to claim 1 , wherein at least one of the groups containing an ethylenically unsaturated bond bonded to the cyclic skeleton is a (meth)acryloyl group, a vinyl group, an allyl group, or an acryl group. 3 . The binder polymer for a nonaqueous secondary battery according to claim 1 , wherein at least one of the groups containing an ethylenically unsaturated bond bonded to the cyclic skeleton is a (meth)acryloyl group. 4 . The binder polymer for a non-aqueous secondary battery according to claim 1 , wherein at least one of the cyclic skeletons in the cyclic molecule of the monomer (a3) is a crown ether skeleton, a cyclic siloxane skeleton, or a cyclic oligosaccharide skeleton. 5 . The binder polymer for a non-aqueous secondary battery according to claim 1 , wherein at least one of the cyclic skeletons in the cyclic molecule of the monomer (a3) is an α-cyclodextrin skeleton. 6 . The binder polymer for a non-aqueous secondary battery according to claim 1 , wherein at least one of the terminal blocking groups is a dinitrophenyl group, an adamantyl group, a trityl group, or a derivative group of any one of these groups. 7 . The binder polymer for a non-aqueous secondary battery according to claim 1 , wherein at least one of the terminal blocking groups is an adamantyl group.
8. The binder polymer for non-aqueous secondary batteries according to claim 1, wherein the chain molecule is at least one selected from polyethylene glycol, polypropylene glycol, polyisoprene, polyisobutylene, polybutadiene, polytetrahydrofuran, polyacrylate, polydimethylsiloxane, polyethylene, and polypropylene. 9 . The binder polymer for a non-aqueous secondary battery according to claim 1 , wherein the chain molecule is polyethylene glycol. 10 . The binder polymer for a non-aqueous secondary battery according to claim 1 , wherein the number average molecular weight of the chain molecule is 5,000 to 50,000.
11. The binder polymer for non-aqueous secondary batteries according to claim 1, further comprising a fourth structural unit derived from monomer a4, The monomer a4 is a compound having multiple independent ethylenically unsaturated bonds. 12 . The binder polymer for a non-aqueous secondary battery according to claim 11 , wherein a content of the fourth structural unit in all structural units is 0.010 mass % or more and 10 mass % or less.
13. The binder polymer for a non-aqueous secondary battery according to claim 1, wherein at least one of the monomers a1 is an aromatic compound having an ethylenically unsaturated bond. The content of the structural unit derived from the aromatic compound having an ethylenically unsaturated bond in all the structural units is 41% by mass or more. 14 . The binder polymer for a non-aqueous secondary battery according to claim 1 , wherein a content of the second structural unit in all structural units is 0.10 mass % or more and 20 mass % or less. 15 . The binder polymer for a non-aqueous secondary battery according to claim 1 , wherein a content of the third structural unit in all structural units is 0.010 mass % or more and 15 mass % or less. 16 . The binder polymer for a non-aqueous secondary battery according to claim 15 , wherein the content of the third structural unit in all structural units is 4.1% by mass or more. 17 . A binder composition for a non-aqueous secondary battery, comprising: dispersed particles containing the binder polymer for a non-aqueous secondary battery according to claim 1 ; and an aqueous medium. 18 . The binder composition for a non-aqueous secondary battery according to claim 17 , wherein an average particle diameter d50 of the dispersed particles is 0.18 μm or more and 1.0 μm or less.
19. A slurry for non-aqueous secondary battery electrodes, comprising the binder polymer for non-aqueous secondary batteries according to any one of claims 1 to 16, an electrode active material, and an aqueous medium, The aqueous medium is one selected from the group consisting of water, a hydrophilic solvent, and a mixture containing water and a hydrophilic solvent. 20 . A non-aqueous secondary battery electrode, comprising the binder polymer for a non-aqueous secondary battery according to claim 1 . 21 . A non-aqueous secondary battery comprising the non-aqueous secondary battery electrode according to claim 20 .
22. A method for producing a binder polymer for a non-aqueous secondary battery, characterized in that: A polymerization step of copolymerizing monomers including monomer a1, monomer a2, and monomer a3 is provided, The monomer a1 is a nonionic compound having only one ethylenically unsaturated bond. The monomer a2 is a compound having a carboxyl group and only one ethylenically unsaturated bond, The monomer a3 is a polyrotaxane having a cyclic molecule and a chain molecule, wherein the cyclic molecule has a cyclic skeleton to which a group containing an ethylenically unsaturated bond is bonded, and the chain molecule penetrates the opening of the cyclic molecule and has end-capping groups at both ends.
Citation Information
Patent Citations
Binder for lithium ion secondary battery electrodes, slurry obtained by using the binder for electrodes, electrodes obtained by using the slurry, and lithium ion secondary battery obtained by using the electrodes
JP2011243464A
Lithium ion secondary battery
JP2014239070A
Resin emulsion for coating and method for producing the same
JP2019116594A
Vein imaging device and vain imaging method
JP2022126956A